'God send vs þe dew of heuene' in Oxford, Bodleian Library, MS Digby 172: A new edition of a Middle English-Latin lyric, with commentary - Burns, RA (Taylor & Francis (Routledge), 2024)
This article presents a new and extended edition of ‘God send vs þe dew of heuene’, with a full translation and commentary. This Middle English-Latin bilingual lyric of the fourteenth century is written haphazardly in the upper margin of Oxford, Bodleian Library, MS Digby 172, fol. 55 r, and is annotated with alterations and variants indicative of compositional and perhaps compilational activity. Through literary analysis of the lyric’s prosodic form and homiletic context, and through a careful assessment of its mise-en-page and palaeographic features, this article produces a dynamic edition which preserves the layers of accretion and revision present in the manuscript text.